The Effect Of Product Quality And Packaging Prices Of Herbal Drinks On Customer Satisfaction Among Generation Z At Warkop Maju Rorotan, North Jakarta - Muhammad Rafi; Koerniawan Hidajat (UNIVED Press, 2026)
This research serves to find out and explain the ability of the influence of product quality on customer satisfaction, as well as to find out and explain the ability to influence price on customer satisfaction. Herbal beverage packaging in Indonesia, which is influenced by changes in the lifestyle of people who are aware of health and the environment. Packaging of herbal drinks, such as ginger, is a better alternative choice than sweet or carbonated drinks, especially among Generation Z. Warkop Maju Rorotan North Jakarta innovates by selling packaging of herbal drinks to attract the younger generation, with a focus on product quality for customer satisfaction. This research also applies SEM and PLS methods to analyze the data, which allows researchers to obtain the value of variables that are relevant for predictions. Thus, the results of this research are expected to provide new insights in the development of herbal beverage products and improve the quality of educational institutions through scientific work at the University of August 17, 1945 Jakarta.